2014
DOI: 10.1186/ar4550
|View full text |Cite
|
Sign up to set email alerts
|

Classification and characteristics of Japanese patients with antineutrophil cytoplasmic antibody-associated vasculitis in a nationwide, prospective, inception cohort study

Abstract: IntroductionWe investigated the clinical and serological features of patients with antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) in Japan using data from a nationwide, prospective, inception cohort study.MethodsIn total, 156 Japanese patients with newly diagnosed AAV were classified according to the European Medicines Agency (EMEA) algorithm with exploratory surrogate markers for AAV-related non-granulomatous pulmonary lesions, predefined as alveolar haemorrhage and interstitial lung d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
134
3
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 176 publications
(162 citation statements)
references
References 30 publications
23
134
3
2
Order By: Relevance
“…In the RemIT-JAV study, we confirmed that MPO-ANCA-positive MPA/renal limited vasculitis RLV) was the most common form of AAV in Japanese patients and revealed that one-half of patients with GPA had MPO-ANCA positivity and that interstitial lung disease (ILD) was an important clinical manifestation in Japanese patients with AAV [5,6]. This high MPO-ANCA positivity in patients with GPA was also confirmed in a recent retrospective report [7].…”
Section: Introductionsupporting
confidence: 66%
See 1 more Smart Citation
“…In the RemIT-JAV study, we confirmed that MPO-ANCA-positive MPA/renal limited vasculitis RLV) was the most common form of AAV in Japanese patients and revealed that one-half of patients with GPA had MPO-ANCA positivity and that interstitial lung disease (ILD) was an important clinical manifestation in Japanese patients with AAV [5,6]. This high MPO-ANCA positivity in patients with GPA was also confirmed in a recent retrospective report [7].…”
Section: Introductionsupporting
confidence: 66%
“…The patients with threatened vital organ function were classified as having a generalized disease, and the patients with organ failure were classified as having severe disease. Detailed definitions of disease severity were described in our previous report [5].…”
Section: Disease Severitymentioning
confidence: 99%
“…Although this has been previously reported in the literature (4,5,7,8,(27)(28)(29)(30)(31), we analyzed CT images in sequential hospital-based patients before they received treatment and determined the prevalence of each imaging component of ILD (Table 2). Ground-glass opacity was the most prevalent component, which indicates that a large proportion of MPA patients have an active inflammatory process in the lungs before they receive treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Pauci-immune type necrotizing crescentic glomerulonephritis is common in GPA, as well as MPA. In the Japanese cohort, 54.6% of the patients with GPA are positive for serum MPO-ANCA with frequency noted to be higher than in western countries [1]. Lastly, EGPA is an eosinophil-rich and necrotizing granulomatous vasculitis that predominantly affects small to medium-sized vessels.…”
Section: Introductionmentioning
confidence: 96%
“…MPA is a necrotizing vasculitis that preferentially affects the renal glomeruli with few immune deposits. In Japan, the majority of patients with MPA are positive for serum myeloperoxidase (MPO)-ANCA [1]. Inflammation that is not centered on the vessels, including granulomatous inflammation, is generally absent.…”
Section: Introductionmentioning
confidence: 99%